Fusion Model for Traffic Sign Detection, Tracking and Recognition - Dhingra, Shubham; Saranya, G; Diwakar, Shalini; Kumar, Manish (International Journal of Engineering and Technology, 2018)
A video-input traffic sign recognition is an advanced application which is a part of Intelligent Transport System(ITS) that provides information to the vehicles in order to make them safe and coordinated on road. The approach is to take a video as an input, divide it into series of frames and implement detection and recognition under mobile conditions. There are three major components: 1) detection; 2) recognition; 3) classification. We implement our technology on real data sets to obtain results in real-time manner.Â Â